Project based learning integrated STEM to increase students' scientific literacy of fluid statics topic - Parno, Parno (2020)
Learning in the 21st century deals with literacy skill. In fact, studies investigating Project-Based Learning Integrated Science Technology Engineering and Mathematics (PjBL-STEM) to develop students' scientific literacy are under-explored. This research investigated the impact of PjBL-STEM on students' scientific literacy of Fluid Statics topic in three classes, these are, Experiment (PjBL-STEM), Comparison (PjBL), and Control (traditional). In Quasi-Experimental Nonrandomized Control Pretest-Posttest Design environment, students in PjBL-STEM and PjBL classes made three products (Hartl apparatus, miniature of multi-level parking lot, and simple boat). Fluid Statics Scientific Literacy Test with seven discourses and eleven essay items was used with 0.908 Cronbach's alpha reliability. Data was analysed with one-way ANOVA, post hoc Tukey, N-gain, and Cohen's effect size. The results showed that three classes had significantly different scientific literacy, where PjBL-STEM was the highest and PjBL class is higher than the traditional class. The literacy improvement of Experiment class included in "high" category and both Comparison and Control classes were in "medium" category. The effect of operational implementation of all pairs of classes belonged in "very large" category in the enhancement of students' scientific literacy. Students' response was similar in PjBL-STEM and PjBL classes, though it is higher than traditional class in the final questionnaire.